(untitled) (LEARNing Landscapes, 2009)
The author, a successful academic, admits that reading for him, as an extrovert, has been primarily considered a painful experience and throughout his schooling, he often viewed it as punishment. Through the needs of his nephew, the author and his brother, another non-reader, embark on a series of reading adventures that bring reading for pleasure into their lives and model it for family and friends. The article provides a justification for personal narrative as form of research and concludes with some insights on informal literacy advocacy.